Implementation of Government Regulation Number 23 of 2018 Related to Income Earned by Taxpayers in The Msme Sector - Tahir, Ayani Dinasti Azira; Rustan, Fajar Eko Purnomo; Sahib, Muhammad Khaedar; Mira, Mira (Jurnal Manajemen, 2023)
MSMEs have relatively contributed to the pressure during the pandemic now. This study aims to find out how the implementation related to government regulation number 23 of 2018 income earned by the MSME sector taxpayers in the Regency Bantaeng . This type of research used is descriptive method qualitative . This research data is sourced from the results of interviews with MSME tax payers and KPP Pratama employees who were processed . Data collection methods used in this research are observations, interviews, and document studies in which the author in a manner comes to location research The results of this study show a deep bottom application related to government regulation number 23 of 2018 income derived by taxpayers from the MSME sector KPP Pratama has tried to maximize the application of the 0.5% final income tax but not yet fully effective by looking at the realization of MSME tax data collection alone. As for who became a limitation in this study is limited to the territory of being the subject of this study, where this study is only for SMEs in the regional districts of Bantaeng just. And the characteristics / advantages of this study lie in the observation period related to the actual latest tax data that is year 2021